Association between higher dietary lycopene intake and reduced depression risk among American adults: evidence from NHANES 2007–2016 - Li, Xiaosong; Lan, Yuru (Frontiers in Nutrition, 2025)
IntroductionAlthough previous researches have suggested that certain dietary nutrients, such as carotenoids, have an effect on depression, epidemiological evidence on the relationship between lycopene and depression remains limited. This study aimed to investigate the association between dietary lycopene intake and depression risk in American adults.MethodsData from 18,664 participants in the National Health and Nutrition Examination Survey (NHANES, 2007–2016) were analyzed, with depression defined by a nine-item Patient Health Questionnaire (PHQ-9) score ≥ 10. Dietary lycopene intake was estimated from the mean of two 24-h dietary recalls. Binary logistic regression and restricted cubic spline (RCS) models were employed to assess the relationship.ResultsDepression prevalence was 8.98%, and adjusted analyses indicated that higher dietary lycopene intake was significantly associated with a reduced depression risk compared to the lowest quartile (ORs for the second, third, and fourth quartiles: 0.851 [95% CI, 0.737–0.982], 0.829 [95% CI, 0.716–0.960], and 0.807 [95% CI, 0.695–0.938], respectively). Additionally, a U-shaped relationship was observed, with a reduction in depression risk associated with dietary lycopene intake ranging from 0 to 10,072 μg/d (P-non-linear = 0.017).DiscussionThis study suggested that higher dietary lycopene intake may confer a protective effect against depression in American adults.